(untitled) (Fiep Bulletin - online, 2011)
Cardiac arrhythmias are alterations in the cardiac rhythm and/or frequency, being many of them of a malignant characteristic, and responsible for the death of millions of individuals. Therefore, it is most important that nurses working in Urgency and Intensive Care Units can recognize and act precisely when facing cardiac arrhythmias, thus affording a qualified assistance to the patient. AIM: Evaluate nurses’ knowledge about cardiac arrhythmias as they act in urgency and intensive care units. METHODOLOGY: This was an exploratory, descriptive research, with a quanti-qualitative approach, occurred at the Police Hospital General Edson Ramalho in October, 2010. The sample comprised 22 nurses. Data collection was done by an objective/subjective questionnaire. Quantitative data were analyzed to form a data base, statistically dealt with by means of the software SPSS, version 17.0. Subjective questions were qualitatively analyzed, by using the Collective Subject Discourse Analysis. RESULTS: The sample contained 22.7% male nurses and 77.3% female nurses. It was observed that 50% of the nurses were between 20-30 years old. 50% of the total are post-graduate. As for the nurses’ specific knowledge about arrhythmias considered of emergency, 86.4% answered correctly about ventricular tachycardia and fibrillation, and pulse less electrical activity, and 95.4% about asystole. CONCLUSION: We came to the conclusion that the researched population demonstrated the necessary knowledge when facing the main cardiac arrhythmias considered of emergency. However, they did not show the same domain about other types of arrhythmia, thus proving their need for refresher courses, for the construction of knowledge and application in their daily practices.